Fates of Paleo‐Antarctic Bottom Water During the Early Eocene: Based on a Lagrangian Analysis of IPSL‐CM5A2 Climate Model Simulations. Issue 1 (9th January 2021) - Zhang, Yurui; Grima, Nicolas; Huck, Thierry
Abstract: Both deepwater formation and the obduction processes converting dense deep water to lighter surface water are the engine for the global meridional overturning circulation (MOC). Their spatio‐temporal variations effectively modify the ocean circulation and related carbon cycle, which affects climate evolution throughout geological time. Using early‐Eocene bathymetry and enhanced atmospheric CO2 concentration, the IPSL‐CM5A2 climate model has simulated a well‐ventilated Southern Ocean associated with a strong anticlockwise MOC. To trace the fates of these paleo‐Antarctic Bottom Water (paleo‐AABW), we conducted Lagrangian analyses using these IPSL‐CM5A2 model results and tracking virtual particles released at the lower limb of the MOC, defined as an initial section at 60°S below 1, 900 m depth. Diagnostic analysis of these particles trajectories reveals that most paleo‐AABW circulates back to the Southern Ocean through either the initial section (43%) or the section above (31%), the remaining (>25%) crossing the base of the mixed layer mostly in tropical regions (up to half). The majority of water parcels ending in the mixed layer experience negative density transformations, intensified in the upper 500 m and mostly occurring in tropical upwelling regions, with a spatial pattern consistent with the wind‐driven Ekman pumping, largely determined by the Eocene wind stress and continental geometry. In the same way as present‐day North Atlantic Deep Water upwells in the Southern Ocean, our results suggest that the strong tropical and equatorial upwelling during the Eocene provides an efficient pathway from the abyss to the surface, but at much higher temperature, with potential implications for the oceanic carbon cycle. Key Points: A coupled climate simulation of the early Eocene shows a single intense overturning cell originating in the Southern Ocean Lagrangian analysis of this paleo‐Antarctic Bottom Water reveals a major route to the surface mixed layer, with implications for carbon cycle This upwelling mainly occurs in equatorial and tropical regions, in relation with the spatial pattern of the wind‐driven Ekman pumping